CTSA recruitment resources: An inventory of what CTSA hubs are currently offering - Niyibizi, Nyiramugisha (J Clin Transl Sci, 2020)
INTRODUCTION: In order to tackle the challenge of efficiently meeting clinical research accrual goals, many Clinical and Translational Science Award (CTSA) recipients have developed recruitment support mechanisms and resources to help investigators successfully recruit study participants. Disseminating recruitment best practices and developing collaborations between institutions can help strengthen recruitment capabilities and methodologies currently utilized by researchers. METHODS: To discover what recruitment resources and mechanisms CTSAs are using, the CTSA Recruitment and Retention working group developed an electronic survey, which was distributed to CTSAs between May and July 2019. The survey contained over 50 multiple choice and short answer questions, with 40 of the 64 CTSA institutions completing the survey. Institutions reported on registries, feasibility assessment tools, clinical trial listings, experience recruiting special populations, program operations and evaluation, workforce education, social media use, and other recruitment resources. RESULTS: All respondents currently utilize some form of a volunteer registry; over 80% of the CTSAs provide investigators with recruitment consultations, feasibility assessments, study listings, and electronic health record (EHR) utilization; 73% assist with study materials; 47% offer social media assistance. Many institutions reported success in recruiting patients and healthy volunteers, but difficulty in recruiting special populations such as non-English-speaking persons and rural populations. Additional recruitment tools included use of the EHR to facilitate recruitment, use of registries, and use of social media to engage participants. CONCLUSIONS: Areas of opportunity or growth include the development of innovative solutions in the areas of social media advertising, identification of participants from special populations, and research volunteer engagement.